The Concept of Love as Verbalized in the Phraseology of Standard Serbian and Jargon - Dragić, Mila R. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
This paper aims to examine the various linguistic means by which the concept of love is verbalized in modern Serbian, in order to uncover the cognitive mechanisms that underlie its conceptualization. The corpus consists of phraseological units that express the emotion itself or different aspects of love relationships. These expressions reflect the social and cultural heritage, as well as the collective mentality and traditional values of the broader language community. The corpus also includes jargonisms that represent innovative units of informal communication and reflect the attitudes and values inherent in youth social groups, where they are actively created and used. This approach enables the exploration of both conventional and unconventional aspects of the concept of love. The method used in this research is conceptual analysis, which helps us identify the source domains and conceptual metaphors through which the concept of love is understood, with particular attention to the specificities, similarities, and differences in how these mechanisms are realized across different types of linguistic expressions.